A spontaneously immortalized Schwann cell line from aldose reductase‐deficient mice as a useful tool for studying polyol pathway and aldehyde metabolism. Issue 6 (16th January 2018) - Niimi, Naoko; Yako, Hideji; Takaku, Shizuka; Kato, Hiroshi; Matsumoto, Takafumi; Nishito, Yasumasa; Watabe, Kazuhiko; Ogasawara, Saori; Mizukami, Hiroki; Yagihashi, Soroku; Chung, Sookja K.; Sango, Kazunori
Abstract: The increased glucose flux into the polyol pathway via aldose reductase (AR) is recognized as a major contributing factor for the pathogenesis of diabetic neuropathy, whereas little is known about the functional significance of AR in the peripheral nervous system. Spontaneously immortalized Schwann cell lines established from long‐term cultures of AR‐deficient and normal C57BL/6 mouse dorsal root ganglia and peripheral nerves can be useful tools for studying the physiological and pathological roles of AR. These cell lines, designated as immortalized knockout AR Schwann cells 1 (IKARS1) and 1970C3, respectively, demonstrated distinctive Schwann cell phenotypes, such as spindle‐shaped morphology and immunoreactivity to S100, p75 neurotrophin receptor, and vimentin, and extracellular release of neurotrophic factors. Conditioned media obtained from these cells promoted neuronal survival and neurite outgrowth of cultured adult mouse dorsal root ganglia neurons. Microarray and real‐time RT‐PCR analyses revealed significantly down‐regulated mRNA expression of polyol pathway‐related enzymes, sorbitol dehydrogenase and ketohexokinase, in IKARS1 cells compared with those in 1970C3 cells. In contrast, significantly up‐regulated mRNA expression of aldo‐keto reductases (AKR1B7 and AKR1B8) and aldehyde dehydrogenases (ALDH1L2, ALDH5A1, and ALDH7A1) was detected in IKARS1 cells compared with 1970C3 cells. Exposure to reactive aldehydes (3‐deoxyglucosone, methylglyoxal, and 4‐hydroxynonenal) significantly up‐regulated the mRNA expression of AKR1B7 and AKR1B8 in IKARS1 cells, but not in 1970C3 cells. Because no significant differences in viability between these two cell lines after exposure to these aldehydes were observed, it can be assumed that the aldehyde detoxification is taken over by AKR1B7 and AKR1B8 in the absence of AR. Abstract : Aldose reductase (AR) is involved in the pathogenesis of diabetic neuropathy via activating polyol pathway, whereas it plays a role in aldehyde detoxification. We observed down‐regulation of polyol pathway‐related enzyme mRNA expression, and up‐regulation of aldo‐keto reductase and aldehyde dehydrogenase mRNA expression in AR‐deficient Schwann cells IKARS1 as compared with those in wild‐type Schwann cells 1970C3 . The up‐regulated enzymes might take over AR detoxifying function.